2002
DOI: 10.1073/pnas.072033799
|View full text |Cite
|
Sign up to set email alerts
|

A physiologic signaling role for the γ-secretase-derived intracellular fragment of APP

Abstract: Presenilins mediate an unusual intramembranous proteolytic activity known as ␥-secretase, two substrates of which are the Notch receptor (Notch) and the ␤-amyloid precursor protein (APP). ␥-Secretase-mediated cleavage of APP, like that of Notch, yields an intracellular fragment [APP intracellular domain (AICD)] that forms a transcriptively active complex. We now demonstrate a functional role for AICD in regulating phosphoinositide-mediated calcium signaling. Genetic ablation of the presenilins or pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
197
2
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(212 citation statements)
references
References 31 publications
11
197
2
2
Order By: Relevance
“…Under these conditions we did not observe differential regulation of previously described AICD target genes such as KAI1 (Table 2). We could not detect regulation of other putative target genes, including SERCA2B (Leissring et al, 2002) or GSK3␤ (Kim et al, 2003). However, our data are in agreement with other groups who could not detect AICD-dependent regulation of these genes in AICD/FE65 transgenic mice (Ryan and Pimplikar, 2005) or in cell lines with pharmacological inhibition or deficiency of ␥-secretase activity (Hebert et al, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…Under these conditions we did not observe differential regulation of previously described AICD target genes such as KAI1 (Table 2). We could not detect regulation of other putative target genes, including SERCA2B (Leissring et al, 2002) or GSK3␤ (Kim et al, 2003). However, our data are in agreement with other groups who could not detect AICD-dependent regulation of these genes in AICD/FE65 transgenic mice (Ryan and Pimplikar, 2005) or in cell lines with pharmacological inhibition or deficiency of ␥-secretase activity (Hebert et al, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…The 99 amino acid C-terminal fragment of APP generated by BACE cleavage can be internalized and further processed by γ-secretase to produce Aβ40/42 in endocytic compartments. Cleavage of C99 by γ-secretase liberates an APP intracellular domain (AICD) that can translocate to the nucleus where it may regulate gene expression including the induction of apoptotic genes 66 . Cleavage of APP/C99 by caspases produces a neurotoxic peptide (C31) 67 .…”
Section: Boxmentioning
confidence: 99%
“…However, reports on the molecular mechanism that underlies presenilin FAD-dependent Ca 2ϩ dyshomeostasis have been inconclusive and often contradictory. It has been suggested that changes in ␥-secretase-mediated production of the AICD are responsible for aberrant Ca 2ϩ signaling observed in cells expressing FAD mutant presenilin (42). However, Herms and colleagues (43) have demonstrated that CCE deficits associated with FAD mutant presenilins occur even in the absence of APP (and AICD).…”
Section: Discussionmentioning
confidence: 99%